Enhancing Memorize the Qur'an through Qur'ans Aplications and Different Students' Critical Thinking Levels - Rt Bai Rohimah; Taswiyah; Omah Mukarromah -; Ahmad Maujud (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
The memorization of the Qur'an (ḥifẓ al-Qur'ān) has been a central aspect of Islamic education for centuries. The purpose of this study is to analyze the differences in memorizing the Quran using digital and murrotal Qurans, critical thinking of students at different levels and the influence of interaction between memorizing the Quran using digital and murrotal Qurans on memorizing the Quran. Quantitative methodology was implemented in the present research, using a quasi-experimental design. This design integrates a non-equivalent control group methodology with a two-way factorial design (2 x 3 ANOVA). This investigation employed a sample of 300 students. A total of 150 participants comprised each cohort. The participants of this investigation were first-year pupils at Sultan Ageng Tirtayasa University in Banten. This research yielded three principal findings: 1) A disparity exists in the memorisation capabilities of students utilising digital Qur'an against auditory murrotal. 2) There exists a disparity in the capacity to memorise the Qur'an among pupils with high, medium, and low levels of critical thinking. 3) An interaction exists between the utilisation of digital Qur'an and audio murrotal, influencing students' critical thinking regarding their capacity to memorise the Qur'an. The proposed study presents novelty by addressing this gap, offering a comparative analysis of the role that critical thinking plays in memorizing the Qur'an using digital and audio murottal Qur'ans. The novelty lies in integrating cognitive psychology with Qur'an education, proposing that students with higher critical thinking skills may engage more deeply with the digital Qur'an, thereby enhancing their retention.